Fluid replacement and respiratory function: comparison of whole blood with colloid and crystalloid. Issue 1 (January 2016) - Fodor, Gergely H.; Babik, Barna; Czövek, Dorottya; Doras, Camille; Balogh, Ádám L.; Bayat, Sam; Habre, Walid; Peták, Ferenc
Abstract : BACKGROUND: Fluid replacement with blood products, colloids and crystalloids is associated with morbidity and mortality. Despite this, the consequences of fluid administration on airway and respiratory tissue properties are not fully understood. OBJECTIVE: Comparison of respiratory effects of fluid replacement with autologous blood (Group B), colloid (HES 6% 130/0.4, Group CO) or crystalloid solution (NaCl 0.9%, Group CR) after haemorrhage with separate assessments of airway resistance and respiratory tissue mechanics. DESIGN: A randomised study. SETTING: An experimental model of surgical haemorrhage and fluid replacement in rats. PARTICIPANTS: Anaesthetised, ventilated rats randomly allocated into three groups (Group B: n  = 8, Group CO: n  = 8, Group CR: n  = 9). INTERVENTION: Animals were bled in six sequential steps, each manoeuvre targeting a loss of 5% of total blood volume. The blood loss was then replaced stepwise in a 1 : 1 ratio with one of the three fluids. MAIN OUTCOME MEASURE: After each step, airway resistance (Raw), tissue damping and elastance (H) were determined by forced oscillations. Oedema indices from lung weights and histology were also measured. RESULTS: Raw (mean ± SD) decreased in all groups following blood loss (−20.3 ± 9.5% vs. baseline, P  < 0.05), and remained low following blood replacement (−21.7 ± 14.5% vs. baseline, P  < 0.05), but was normalised by colloid (5.5 ± 10.7%, NS). Crystalloid administration exhibited an intermediate reversal effect (−8.4 ± 14.7%, NS). Tissue viscoelasticity increased following both blood loss and replacement, with no evidence of a significant difference in H between Groups CO and CR. More severe oedema was observed in Groups CR and CO than in Group B ( P  < 0.05), with no difference between the colloid and crystalloid solutions. CONCLUSION: This model, which mimics surgical haemorrhage, yields no evidence of a difference between colloids and crystalloids with regard to the pulmonary consequences of blood volume restoration. Functional changes in the lung should not be a key concern when choosing fluid replacement therapy with these solutions.